2019
DOI: 10.1109/access.2019.2930562
|View full text |Cite
|
Sign up to set email alerts
|

A new Approach for the Modulus-Based Matrix Splitting Algorithms

Abstract: We investigate the modulus-based matrix splitting iteration algorithms for solving the linear complementarity problems (LCPs) and propose a new model to solve it. The structure of the new model is straightforward and can be extended to other issues of type of complementarity. Convergence analysis of the new approach for the symmetric positive definite matrix is also discussed. The numerical results of the proposed approach are compared with the existing algorithms to show its efficiency. INDEX TERMS Linear com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In [24], El foutayeni and Khaladi have shown that the linear complementarity problem LCPðM, qÞ is completely equivalent to finding the fixed point of the map x = max ð0, ðI − MÞx − qÞ, and they showed that to find an approximation of the solution to the second problem, they proposed an algorithm that starts from an arbitrary interval vector X ð0Þ , then they generalize a sequence of the interval vector ðX ðkÞ Þ k=1,⋯ that converges to the best solution of linear complementarity problems. Newly, in [30], for solving the linear complementarity problem, Wang et al [31] propose an interior point method to find the solution of the linear complementarity problem, where the matrix is a real square hidden Z-matrix. In this context, we can see the works [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [24], El foutayeni and Khaladi have shown that the linear complementarity problem LCPðM, qÞ is completely equivalent to finding the fixed point of the map x = max ð0, ðI − MÞx − qÞ, and they showed that to find an approximation of the solution to the second problem, they proposed an algorithm that starts from an arbitrary interval vector X ð0Þ , then they generalize a sequence of the interval vector ðX ðkÞ Þ k=1,⋯ that converges to the best solution of linear complementarity problems. Newly, in [30], for solving the linear complementarity problem, Wang et al [31] propose an interior point method to find the solution of the linear complementarity problem, where the matrix is a real square hidden Z-matrix. In this context, we can see the works [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Newly, in [30], for solving the linear complementarity problem, Wang et al [31] propose an interior point method to find the solution of the linear complementarity problem, where the matrix is a real square hidden Z-matrix. In this context, we can see the works [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Further discussing the modulus-based matrix splitting iteration method and its various versions, one can see [11][12][13][14][15][16][17] for more details. In addition, for other forms of iteration methods, one can see [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%